Optimasi Keel Cooler pada Sistem Pendingin Mesin Induk Kapal - Nikmatullah, Muhammad Iqbal; Ahyuni, Sri; Klara, Sherly; Mahmuddin, Faisal; Eka, A. Erwin (Jurnal Penelitian Enjiniring, 2024)
OT ship Skylie is a type of tanker that uses a keel cooler as its engine cooling system. The keel cooler is a new type of heat exchanger that is applied in the shipping world because it is installed externally on the ship's hull below the surface of the water. This study aims to determine the optimum length dimensions of the keel cooler system. Methods of analysis and simulation using Ansys software. Based on the calculation results on several variations of the keel cooler length dimensions, the greatest heat transfer value is 6.655 x 105 W in the length variation II with an inlet pipe size of 53.85 meters, an outlet pipe of 47 meters, and a pipe length of 44 meters with the greatest effectiveness value of 80.138%. Meanwhile, the lowest heat transfer was 4,503 x 105 W in the length variation III with an inlet pipe size of 37.85 meters, 31 meters outlet pipe and 28 meters long pipe with the lowest effectiveness value of 79.910%. Therefore it can be concluded that the longer the dimensions of the keel cooler, the greater the heat transfer value and effectiveness and the size variations studied meet the standard values ​​​​for the effectiveness of using the keel cooler.